2014
DOI: 10.1159/000363128
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative White Matter Lesions Are Independent Predictors of Long-Term Survival after Internal Carotid Endarterectomy

Abstract: Background: Cerebral white matter lesions (WMLs) predict long-term survival of conservatively treated acute stroke patients with etiology other than carotid stenosis. In carotid endarterectomy patients, WMLs are associated with severe carotid stenosis and unstable plaques, with the risk of perioperative complications and with increased 30-day perioperative risk of death. However, no data exist on their effect on postoperative long-term survival, a factor important when considering the net benefit from carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The finding that increased post-operative long term risk of cardiovascular death in symptomatic patients undergoing CEA is associated with reported SVD is in line with a previous small study, 8 which showed that CEA patients (predominantly symptomatic) with any quantified WML on preoperative brain CT had an increased five year mortality risk (predominantly of cardiovascular origin). It is now shown that, also based on standard brain imaging reports, SVD can be used as a predictor of cardiovascular death.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The finding that increased post-operative long term risk of cardiovascular death in symptomatic patients undergoing CEA is associated with reported SVD is in line with a previous small study, 8 which showed that CEA patients (predominantly symptomatic) with any quantified WML on preoperative brain CT had an increased five year mortality risk (predominantly of cardiovascular origin). It is now shown that, also based on standard brain imaging reports, SVD can be used as a predictor of cardiovascular death.…”
Section: Discussionsupporting
confidence: 90%
“…Yet, previous studies that did investigate the correlation between (semi-) quantitative WML measures and outcome in patients undergoing CEA used trained radiologists for assessment of these study parameters which has the disadvantage of not being part of standard clinical practice. 3,8,9 Fourth, only symptomatic patients were included, but assessment of peri-operative risk in asymptomatic patients may be even more relevant in the ongoing discussion about whether or not to perform revascularisation procedures in these patients. Finally, stroke was observed less frequently for excluded patients than in included patients (see Table S4), mainly because imaging reports were not attached in the referral from other hospitals.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…White matter lesions (WML) are a surrogate for cerebral small vessel disease (SVD), which is the major cause of accumulating vascular burden in aging populations. Severe WML in stroke patients are associated with a risk of complications after thrombolysis [1] and poor prognosis after carotid endarterectomy [2]. Other well-documented consequences of severe WML are cognitive impairment, gait disturbances, depression, urine incontinence, and the eventual loss of independence and risk for permanent institutionalization [3,4].…”
Section: Introductionmentioning
confidence: 99%